Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Usaha Tani Durian - Sutaminingsih, Luh; Sujana, Nyoman (Ekuitas: Jurnal Pendidikan Ekonomi, 2020)
The objective of this research is to discover factors which influence revenue of Durian farming business at Dusun Witajati Desa Selat, and to figure out dominant elements controlling the farmers’ income. This is categorized as a factorial research. The subjects of this research are 30 farmers at Dusun Witajati Desa Selat, while the objects are factors that affect the revenue of Durian farming business. The data collecting method conducted in this research is interview and documentation. A program for analysing factors by SPSS 16.0 for windows is applied to analyse the data. The results demonstrate two factors affecting the income of farming business at Dusun Witajati Desa Selat, which are internal and external factor. Internal factors consist of family labor with a variance value 41.412%, size of the land with a variance value16.626%, and capital with a variance value13.810%. On the other hand, external factors involve availability of production factor with a variance value 8.688%, costs of production factor with a variance value 7.786%, production demands production factor with a variance value 5.920%, and sale costs production factor with a variance value 5.757%. Consequently, the dominant factors influencing the revenue of Durian farming business at Dusun Witajati Desa Selat are internal factors of family labour with varimax rotation value as 41.412% and size land with varimax rotation value as 16.626%.